Morphometrical and Topographical Anatomy of Position of Nutrient Foramen on Fully Ossified Left Femur (Delta Medical College Journal, 2013)
Background: The femur is the typical long bone of lower limb which extends from the pelvis to the knee. It forms the skeleton of the thigh, bears body weight, supports movement of legs; provide attachment to muscles, form blood cells and acts as a store house for calcium and phosphate. The nutrient foramina are cavities that conduct the nutrient arteries and the peripheral nerves. The majority blood supply for femur originates from the nutrient arteries, mainly during the growing period and during the early phase of ossification. In bone grafts the nutrient blood supply is crucial and it should be preserved in order to promote the fracture healing. Objective: The anatomy of nutrient foramen of femur is very essential for orthopedic & vascular surgeons as well as to radiologists for planning of treatment. Materials and method: This cross sectional study was carried out in the department of Anatomy, Sir Salimullah Medical College, Dhaka, Bangladesh from July 2011 to June 2012. The study comprised 199 fully ossified left sided dry femur of both sex (n=89 male, n=110 female). Sampling technique was purposive. Morphometric and topographic study was carried out on all samples by direct physical and photographic methods. Results: The most common position of nutrient foramen on the shaft of femur was found on the middle 1/5th in both male and female femur (50.78% in male and 56.86% in female respectively). Conclusion: The anatomical knowledge about this study might be useful in certain surgical procedures as well as micro vascular bone transfer to preserve the circulation.DOI: http://dx.doi.org/10.3329/dmcj.v1i1.14970 Delta Med Col J. Jan 2013;1(1):13-15